Poczucie własnej skuteczności jako czynnik różnicujący samodzielne uczenie się studentów - Violetta Rodek, Violetta Rodek (Studia Edukacyjne, 2020)
The article presents empirical and diagnostic research aiming to recognise how a generalised feeling of self-efficacy differentiates students’ independent learning. In the research, Generalized Self – Efficacy Scale (GSES) was applied (according to R. Schwarzer, M. Jeruzalem, in the Polish adaptation by Z. Juczyński) as well as a free-form interview, partially categorised. The study group was composed of 215 intentionally selected pedagogy students, following full-time and part-time courses. The variable adopted in the research differentiates the view of students’ independent learning, mainly in terms of the degree of involvement in their own learning. A high level of self-efficacy seems to be related to regularity, persistence in learning, consistency, the ability to focus on longer periods of learning, as well as the ability to plan and organize one’s own learning process. A generalized sense of self-efficacy, however, is not critical to how we understand the concept of learning, assigning value to it, and the used learning techniques.